Comparison of the QuantiFERON-TB Gold Plus and QuantiFERON-TB Gold In-Tube interferon-γ release assays: A systematic review and meta-analysis - Pourakbari, Babak; Mamishi, Setareh; Benvari, Sepideh; Mahmoudi, Shima (Advances in medical sciences, 2019)
QuantiFERON-TB Gold Plus (QFT-Plus) is a new generation of QuantiFERON assay that differs from QuantiFERON-TB Gold In-Tube test (QFT-GIT). The aim of this study was to compare the performance of the new FDA-approved QFT-Plus interferon (IFN)-γ release assays (IGRAs) with the QFT-GIT version of this assay. We searched all studies published in English in electronic databases, including PubMed, Scopus, and Web of Science. The positive proportion of positive results by QFT-Plus was higher than QFT-GIT in cured tuberculosis (TB) cases (82% vs. 73%). The two tests showed a substantial agreement and the majority of the latent tuberculosis infection (LTBI) subjects responded concomitantly to both QFT-Plus and QFT-GIT. However, QFT-Plus showed a stronger association with surrogate measures of TB suspects than QFT-GIT. The QFT-Plus test demonstrated a higher sensitivity than QFT-GIT in the older adults. The sensitivity, specificity, LR+, LR- and DOR overall were 94% (95% CI 89–97), 96% (95% CI 94–98), 24.4 (95% CI 15–39), 0.05 (95% CI 0.03–0.11) and 414 (95% CI 251–685), respectively. The area under summary ROC curve was 0.99 (95% CI 0.97–0.99). QFT-Plus performs equivalently to the QFT-GIT for detection of patients at risk for LTBI; however, QFT-Plus test had higher sensitivity than the QFT-GIT test, with similar specificity among the older participants. Higher IFN-γ release in TB2 compared to TB1 might be due to recent LTBI.